Feasibility and analysis of a system of two in tandem interferometers for optical coherence tomography - Cerrotta, Santiago (2017)
A signal obtained from a combined system of two interferometers of low coherence in the frequency domain is presented and analyzed. This system allows to expand the range of measurement offered by the conventional optical tomography system of a single interferometer with a spectrometer as a detector.